Nitrous oxide use and psychiatric disorders: a retrospective clinical cohort study on prevalence and patterns - Paetow, Rebecca; Dohrn, Maike Franziska; Finner-Prével, Michelle; Boesehans, Leona; Henning, Dariush; Rust, Marcus; Frodl, Thomas (Frontiers in Psychiatry, 2025)
IntroductionNitrous oxide (N2O) is used for anesthetic purposes but has gained popularity as a recreational substance. Despite its potentially severe adverse effects, knowledge about N2O use within psychiatric populations is limited. This study aimed to evaluate the life-time prevalence and patterns of N2O consumption among patients with psychiatric disorders.MethodsA retrospective observational cohort study was conducted at the Department of Psychiatry, Psychotherapy and Psychosomatics of the Rheinisch-Westfälische Technische Hochschule (RWTH) Aachen University Hospital, involving assessments of N2O use lifetime prevalence among patients in various psychiatric settings over a six-month period in 2024. Further data on demographic characteristics and psychiatric diagnoses were collected from electronic patient records.ResultsOut of 287 screened records, 22 patients (7.67%) reported a N2O use history, with a positive statistical relationship between younger age and positive lifetime prevalence (mean age: 28.14 ± 7.29 years, range 19–48 years, 6/22 female). Most users acquired N2O through low-threshold means such as friends or social events. The predominant psychiatric diagnoses among users included major depressive disorder, cannabis-related disorder and attention deficit and hyperactivity disorder.DiscussionThis study highlights the concerning life-time prevalence of N2O use in a clinical psychiatric sample, emphasizing the need for increased awareness and education regarding its potential risks and side effects. Given the vulnerability of this population to substance-related issues, routine assessment for N2O use should be integrated into standard psychiatric evaluations.